DIGITAL HR - V. V. Maslennikov; Yu. V. Lyandau; I. A. Kalinina (Вестник Российского экономического университета имени Г. В. Плеханова)
The present day digital world creates new realities in organization of managerial structures, whose conventional hierarchical structure becomes outdated. Digitalization of organizational structures of enterprises is realized by a new trend, i. e. Digital HR – digital human resource management. The article describes key aspects of digital HR management, which is necessary to raise the efficiency of HR departments’ functioning and to provide managers and specialists in the field of management with advanced tools for selection of skilled personnel meeting the company requirements. The authors formulated 16 methods, tools and technologies needed for organization of digital HR management, including the on-line structure of the company on digital platform, the system of on-line monitoring of goal attainment, electronic document turnover with digital signature, integration with external digital platforms, the system of on-line personnel training, individual employee adaptation, staff analysis on the basis of mathematic modeling and the use of artificial intellect. As experience shows, as a result of artificial intellect application in HR management the possibility of selecting adequate personnel becomes much higher. Digital management could reduce time necessary for routine operations, which would raise the quality of managerial decision-making and provide the company with highly-qualified staff.